Site-specific radical formation in DNA induced by Cu(II)-H(2)O(2) oxidizing system, using ESR, Immuno-spin trapping, LC/MS and MS/MS - Bhattacharjee, Suchandra (2011)
Oxidative stress-related damage to the DNA macromolecule produces a multitude of lesions that are implicated in mutagenesis, carcinogenesis, reproductive cell death and aging. Many of these lesions have been studied and characterized by various techniques. Of the techniques that are available, the comet assay, HPLC-EC, GC-MS, HPLC-MS and especially HPLC-MS/MS remain the most widely used and have provided invaluable information on these lesions. However, accurate measurement of DNA damage has been a matter of debate. In particular, there have been reports of artifactual oxidation leading to erroneously high damage estimates. Further, most of these techniques measure the end product of a sequence of events and thus provide only limited information on the initial radical mechanism. We report here a qualitative measurement of DNA damage induced by a Cu(II)-H(2)O(2) oxidizing system using immuno spin-trapping (IST) with EPR, MS and MS/MS. The radical generated is trapped by DMPO immediately upon formation. The DMPO adduct formed is initially EPR active but subsequently is oxidized to the stable nitrone, which can then be detected by IST and further characterized by MS and MS/MS.